TINJAUAN KRIMINOLOGIS TERHADAP PEMBUNUHAN ANAK OLEH PELAKU ORANG DENGAN GANGGUAN JIWA SECARA PERIODIK DI DESA NIRANGKLIUNG KABUPATEN SIKKA - Anan, Maria Kasia; Leo, Rudepel Petrus; Amalo, Heryanto (Petitum Law Journal, 2023)
The murder case was carried out by the accused Alosius Lada committing the murder of his nephew Veronika Viance. The main issue in this study is: (1) Are the factors causing the occurrence of murder of children by perpetrators of persons with mental disorders periodically in the village of Nirangkliung, Sikka district? (2) Can a person with a mental disorder committing murder be charged with criminal responsibility? (3) How did the police attempt to persecute the perpetrator of the murder of a child by a person with a mental disorder periodically in the village of Nirangkliung, Sikka district?. This research is empirical law research, which studies and analyzes data obtained from the research site. This research was conducted at the Resor Sikka police. Data processing was done with data obtained from both primary and secondary data and analyzed descriptively-qualitatively. The results of this study show that: (1) The causes of murder of children by perpetrators of people with mental disorders periodically include internal and external factors. Internal factors include revenge, mental/psychological disorder, emotional, and misunderstanding. External factors include environmental influences, and economic factors. (2) Criminal responsibility for the perpetrator of murder by a person with a mental disorder periodically covers Article 44 Paragraph (1) of the Covenant which reads: "Anyone who commits an act that is unacceptable to him because his soul is deficient in growth or disturbed by disease shall not be punished. (3) The attempt by the police to denounce the perpetrator of the murder of a child by a person with a mental disorder periodically constitutes a repressive attempt. In this case, the author suggests that such facilities and facilities as a psychiatric hospital in particular in Kabuparen Sikka are urgently needed. For the health service it is advised to give more socialization to the public about the dangers of a person with a mental disorder wandering in a community settlement.